Undescended Testis Revealing Triorchidism in a Child: A Case Report - Saidou, Barry Thierno; Welle, Ibrahima Bocar; Balla, Keita; Alpha, Mamadou; A. Zeng, Florent Tshibwid; Lamine Sadou, Sacko Mohamed; Alpha, Diallo Mamadou; Agbo-Panzo, Daniel (European Scientific Journal, ESJ, 2022)
Polyorchidism is a rare genitourinary congenital malformation, which diagnosis is generally fortuitous in children. We report the case of a 7-year-old boy admitted to the pediatric surgery service of Donka University Hospital in Conakry for an empty left scrotum. Initially, the diagnosis of left cryptorchidism had prompted orchidopexy by inguinal approach, whose intraoperative exploration revealed two undescended left testicles. The first, located at the deep ring of the inguinal canal, had normal volume, while the second, located in the inguinal canal, was hypotrophic. The orchiectomy of the latter was performed, associated with a dartos-pouch orchidopexy of the testicle of normal volume. After one year of follow-up, no complications were noted.